a ANALISIS PENGELUARAN DAN TINGKAT KESEJAHTERAAN RUMAHTANGGA PETANI KARET DI KECAMATAN KARANG JAYA KABUPATEN MUSI RAWAS UTARA: ANALISIS PENGELUARAN DAN TINGKAT KESEJAHTERAAN RUMAHTANGGA PETANI KARET DI KECAMATAN KARANG JAYA KABUPATEN MUSI RAWAS UTARA - Mayshiska Puspitasari; Ira Primalasari (Politeknik Negeri Lampung, 2021)
This study aimed (1) to measure rubber tappers’household expenditure, (2) to investigate factorswhich affect to the rubber tappers’household expenditure, and (3) to analyzethe wealthy level of rubber tappers’household in Karang Jayasub-districtby using descriptive analysis and multiple linier regression analysis. The samples were 95respondents taken by using survey method. Moreover, the result of the study explained that rubber tappers’household expenditure in Karang Jaya, consist of carbohydrate (44,60%), non-carbohydrate (25,06%), and non-food (30,34%). The carbohydrate expenditure is the highest percentage among others. Wealthy level of this study uses 14 variables; types of wooden wall (35,7%), wells water resources (70,53), firewood recourses (22,11), river sanitation facility (26,32), types of tile floor/cement (68,42), primary education (54), light source of PLN (98,95), car asset (8, 42), motorcycle (85, 26), Polindes(66,54), floor space 8m2(58,87), wear per year (46,27) (1-2)per day (19,23), and incomeRp. 600.000/month (53, 69). Furthermore, factors which affect to the rubber tappers’household expenditure in Karang Jaya are the number of family memberand income which explain Fvalue(141,56) > Ftable(2,47). Therefore, it can be concluded that education, age, income, family numberand space positively and significantlyaffectto the rubber tappers’household expenditure in Karang Jaya. Rvalue square is 0,888, and explains that 88% household expenditure can be explained by age, education, family number, space, and income, while 12%is measured by other variables. Carbohydrate 44,25% is higher than non-carbohydrate and non-food, thus household in Karang Jaya has not been wealthy yet. Keywords: Household expenditurer, rubber farmers, economic welbeing